Children's favorites, volume 1 eaudiobook Disney bedtime favorites and disney storybook collection. - Disney Press (Disney, 2015)
Two story collections in one volume! From Bambi to Aladdin, the best-loved stories of all time are now even better. In Disney Storybook Collection , over twenty stories re-create the movie magic of the most beloved Disney films. Perfect for bedtime, the second edition of the popular Bedtime Favorites storybook collection has nineteen stories to choose from. Updated story selections feature characters from Finding Nemo , Cars 2 , Toy Story 3 , The Lion King , and more.